MANGROVES OF LATIN AMERICA - Molina Moreira, Natalia. (2020)
Mangrove swamps are very important ecosystem; their importance is biological, economic and socio-cultural. It is an essential habitat for the juvenile stages of fish, mollusks, crustaceans, and of many other species. Mangroves maintain a trophic network with bird’s nesting places and, at the same time, they are an important feeding space for other animals. They are natural and irreplaceable filters of sediments and nutrients; this makes them relevant water quality maintenance factors. Mangrove’s thick vegetation and its fabulous root system avoid marine and eolic erosion. Last, mangroves are a source of food and economic maintenance for coastal groups; they also permit plentiful artisan fishing; they supply firewood, charcoal, and lumber for construction; and is source medicinal herbs. Mangroves are magic. The information from the works that were presented in the I Mangroves Congress and that have been given you confirms the above. Mangrove swamps survive, even though they were sacked, cut down and burned year after year. Thanks to the dreaming and brave scientists who prepared the work you have in your hands, we now know that it is possible to restore and reforest mangroves. We also know that humans have finally learned to live in harmony with this ecosystem, but we are also warned of the dangers caused by introduced species. Last, we are also helped to understand the mangroves’ socio-economic importance; and they may also be set as an example of a sustainability model.